INPATIENT MORBIDITY PATTERNS AND HEALTHCARE ACTIVITIES AT PHU YEN TRADITIONAL MEDICINE HOSPITAL BEFORE, DURING, AND AFTER THE COVID-19 PANDEMIC (2020–2023) - Thị Hoàng Oanh, Trần; Hữu Tuấn, Trần (Journal of Health and Aging, 2026)
The COVID-19 pandemic had a widespread impact on all aspects of human life globally, and specifically on Phu Yen Province (now part of eastern Dak Lak Province) in Vietnam. Numerous studies reported significant declines in outpatient visits, hospital admissions, and healthcare service utilization during this period. Evaluating the changes in disease patterns and healthcare service delivery at Phu Yen Traditional Medicine Hospital from 2020 to 2023 is essential for guiding service quality improvements and strengthening preparedness for future public health emergencies. To assess the variation in inpatient disease patterns and describe healthcare service activities at Phu Yen Traditional Medicine Hospital between 2020 and 2023. Study subjects included all inpatient medical records with primary ICD-10 diagnosis codes at Phu Yen Traditional Medicine Hospital from January 1, 2020 to December 31, 2023. Research design: retrospective cross-sectional descriptive study. From 2020 to 2023, musculoskeletal and neurological diseases were the most common. In 2021, COVID-19 cases appeared, with a notable rise in infectious diseases among patients under 15 (94.6%). Clinical staffing remained stable; bed numbers increased from 2022. During the pandemic, patient visits declined but clearly recovered by 2023. Bed occupancy was lowest in 2021 (69.7%) and peaked in 2023 (113.8%). The inpatient disease pattern and hospital service activity at Phu Yen Traditional Medicine Hospital were notably affected by COVID-19, with a sharp decline in 2021 followed by recovery starting in 2022.